Infections as a cause of autoimmune rheumatic diseases - Sakkas, Lazaros I. (Auto Immun Highlights, 2016)
Exogenous and endogenous environmental exposures and particularly infections may participate in the breakage of tolerance and the induction of autoimmunity in rheumatic diseases. Response to infections apparently occurs years before clinical manifestations and features of autoimmunity, such as autoantibodies, are detected years before clinical manifestations in autoimmune rheumatic diseases. In this review, we summarize the current evidence for a potential causal link between infectious agents and rheumatoid arthritis, systemic lupus erythematosus, systemic sclerosis, Sjogren’s syndrome and ANCA-associated vasculitis.